Characterisation of inverse agonism of the orphan-G protein-coupled receptor GPR52 by cannabinoid ligands Cannabidiol and O-1918. Issue 6 (June 2021) - Stott, Lisa A.; Brighton, Cheryl A.; Brown, Jason; Mould, Richard; Bennett, Kirstie A.; Newman, Robert; Currinn, Heather; Autore, Flavia; Higueruelo, Alicia P.; Tehan, Benjamin G.; MacSweeney, Cliona; O'Brien, Michael A.; et al.
Abstract: The identification of cannabinoid ligands Cannabidiol and O-1918 as inverse agonists of the orphan receptor GPR52 is reported. Detailed characterisation of GPR52 pharmacology and modelling of the proposed receptor interaction is described. The identification of a novel and further CNS pharmacology for the polypharmacological agent and marketed drug Cannabidiol is noteworthy. Abstract : GPR52, Inverse agonist, Cannabidiol, CBD, O-1918.